2019
DOI: 10.1186/s12870-019-2156-5
|View full text |Cite
|
Sign up to set email alerts
|

Osa-miR7695 enhances transcriptional priming in defense responses against the rice blast fungus

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression at the post-transcriptional level in eukaryotes. In rice, MIR7695 expression is regulated by infection with the rice blast fungus Magnaporthe oryzae with subsequent down-regulation of an alternatively spliced transcript of natural resistance-associated macrophage protein 6 (OsNramp6). NRAMP6 functions as an iron transporter in rice.ResultsRice plants grown under high iron supply showed blast resistance, which supports that iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Rice seedlings were bottom-watered during the whole experiment. Fertirrigation was supplied at nine days after F. mosseae inoculation, using a modified Hoagland half-strength solution (15 ml, every two days) containing 2.5 mM KNO 3 , 2.5 mM Ca(NO 3 ) 2 ·4H 2 O, 1 mM MgSO 4 ·7H 2 O, 0.5 mM NH 4 NO 3 , 25 μM KH 2 PO 4 , 23.15 μM H 3 BO 3 , 4.55 μM MnCl 2 ·4H 2 O, 0.38 μM ZnSO 4 ·7H 2 O, 0.1 μM CuSO 4 ·5H 2 O, 0.14 μM Na 2 MoO 4 ·2H 2 O, 26 μM Fe-EDDHA, pH 5.5) 65 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice seedlings were bottom-watered during the whole experiment. Fertirrigation was supplied at nine days after F. mosseae inoculation, using a modified Hoagland half-strength solution (15 ml, every two days) containing 2.5 mM KNO 3 , 2.5 mM Ca(NO 3 ) 2 ·4H 2 O, 1 mM MgSO 4 ·7H 2 O, 0.5 mM NH 4 NO 3 , 25 μM KH 2 PO 4 , 23.15 μM H 3 BO 3 , 4.55 μM MnCl 2 ·4H 2 O, 0.38 μM ZnSO 4 ·7H 2 O, 0.1 μM CuSO 4 ·5H 2 O, 0.14 μM Na 2 MoO 4 ·2H 2 O, 26 μM Fe-EDDHA, pH 5.5) 65 .…”
Section: Methodsmentioning
confidence: 99%
“…An average of 32 736 498 clean reads/library were reported (Supplementary Table S6). Raw 125 bp paired-end reads processing and analysis were carried out as previously described 65 . RNA-Seq raw data are available at the NCBI GEO database (https ://www.ncbi.nlm.nih.gov/geo) under the accession number GSE148574.…”
Section: Inoculation With F Mosseae and Growth Of Amf-inoculated Plamentioning
confidence: 99%
See 1 more Smart Citation
“…More than 70 miRNAs respond to M. oryzae or its elicitors (Li et al 2019c). Among these miRNAs, five have been identified as positive regulators in rice blast resistance, namely miR160a, miR162a, miR166k-h, miR398b, and miR7695, whereas eight have been identified as negative regulators, namely miR156, miR164a, miR167d, miR169a, miR319b, miR396, miR1873, and miR444b.2 (Chandran et al 2018;Li et al 2020a;Li et al 2019b;Li et al 2014;Li et al 2017;Salvador-Guirao et al 2018;Sanchez-Sanuy et al 2019;Wang et al 2018b;Xiao et al 2017;Zhang et al 2018b;Zhang et al 2020;Zhao et al 2020;Zhou et al 2020). Obviously, many miRNAs play a role in regulating rice-M. oryzae interactions.…”
Section: Small Rnas In Rice-m Oryzae Pathological Systemmentioning
confidence: 99%
“…Overexpression of miR7695 results in increased iron accumulation, enhanced innate immune responses, and increased accumulation of phytoalexins. Further studies revealed that high concentration of iron improves the expression of OsCPS2 and OsCPS4, which function in the first cyclization steps of phytoalexin biosynthesis, suggesting that miR7695 may promote phytoalexins accumulation via controlling the transport of iron (Campo et al 2013;Sanchez-Sanuy et al 2019;Toyomasu et al 2015). Second, miR398b is a well-elucidated positive regulator in rice resistance against M. oryzae.…”
Section: Small Rnas In Rice-m Oryzae Pathological Systemmentioning
confidence: 99%